Iowa Birdline update, February 17, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for February 17, 1992. The highlights for the update include sightings of an adult Great Black-backed Gull, Iceland Gull and three Long-eared Owls. Also included are handwritten notes with sightings of two Golden Eagles, a Pied-billed Grebe and six to eight Eastern Bluebirds. Epson - sheet feed/flatbed